Re-examining the relationship between invasive lionfish and native grouper in the Caribbean - Valdivia, Abel; Bruno, John F.; Cox, Courtney E.; Hackerott, Serena; Green, Stephanie J. (PeerJ, 2014)
Biotic resistance is the idea that native species negatively affect the invasion success of introduced species, but whether this can occur at large spatial scales is poorly understood. Here we re-evaluated the hypothesis that native large-bodied grouper and other predators are controlling the abundance of exotic lionfish (Pterois volitans/miles) on Caribbean coral reefs. We assessed the relationship between the biomass of lionfish and native predators at 71 reefs in three biogeographic regions while taking into consideration several cofactors that may affect fish abundance, including among others, proxies for fishing pressure and habitat structural complexity. Our results indicate that the abundance of lionfish, large-bodied grouper and other predators were not negatively related. Lionfish abundance was instead controlled by several physical site characteristics, and possibly by culling. Taken together, our results suggest that managers cannot rely on current native grouper populations to control the lionfish invasion.
Keywords: Biotic resistance; Lionfish; Invasive species; Coral reef; Grouper; Caribbean; Predation